2013
DOI: 10.1039/c3an01169k
|View full text |Cite
|
Sign up to set email alerts
|

Combined in situ atomic force microscopy and infrared attenuated total reflection spectroelectrochemistry

Abstract: A novel analytical platform combining infrared attenuated total reflection (IR-ATR) spectroelectrochemistry (SE) with atomic force microscopy (AFM) using a boron-doped diamond (BDD)-modified ATR crystal is presented. The utility of this combination is demonstrated investigating the electrodeposition of a polymer film via IR spectroscopy, while the surface modification is simultaneously imaged by AFM. The ATR waveguide consists of a single-crystal intrinsic diamond overgrown with a homoepitaxial BDD layer (thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…Besides, absorption signals at such wavenumbers were previously observed using the diamond ATR crystal before its doping with boron (see supplementary information of Ref. ). Hence, the bands may well be attributed to changes of the surface absorptive properties of the oxygen‐terminated BDD, impurities present in the original diamond and/or the diamond lattice, though the contribution of the boron‐doping cannot be discarded.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Besides, absorption signals at such wavenumbers were previously observed using the diamond ATR crystal before its doping with boron (see supplementary information of Ref. ). Hence, the bands may well be attributed to changes of the surface absorptive properties of the oxygen‐terminated BDD, impurities present in the original diamond and/or the diamond lattice, though the contribution of the boron‐doping cannot be discarded.…”
Section: Resultsmentioning
confidence: 79%
“…In this regard, spectroelectrochemical studies at BDD electrodes have been shown for evolving changes of the surface termination with the applied potential , and proof‐of‐principle measurements for investigating the transition between hexacyanoferrate (II) and (III) have been demonstrated . In addition, the electropolymerization of PEDOT on BDD has been in situ monitored with AFM and simultaneous IR‐ATR measurements using a combined setup . Changes in the surface morphology and adhesion properties could be correlated with the progression of the polymerization reaction monitored via IR.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials are now being grown [136] in bulk form, as shown in Figure 5.15, for applications such as high-power electronics [33] and as delta-doped layers [137], where thin-film sc BDD is overgrown on insulating diamond, for field effect transistor and Schottky diode applications. One recent article described the overgrowth of a diamondattenuated total reflection prism with homoepitaxial BDD (thickness ∼100 nm, boron dopant density ∼5 × 10 20 B atoms cm −3 ) [138]. The BDD electrode was employed to drive the electrodeposition (ED) of a polymeric species on the BDD 195 surface, monitored by changes in the simultaneously recorded IR signals.…”
Section: Single-crystal Bdd Electrochemistrymentioning
confidence: 99%
“…Diese IR‐transparente Elektrode wurde dann in eine AFM‐Flüssigmesszelle integriert (Abbildung 9). Damit ist die elektrochemisch induzierte Polymerisation von 3,4‐Ethylendioxothiophen (EDOT) simultan infrarotspektroskopisch und topographisch analysierbar 39…”
Section: Analytische Rastersondentechnikenunclassified